Electrochemical Preconcentration Mechanism of Trivalent Lanthanum. Issue 13 (1st January 2018) - Medina, Adan Schafer; Ivory, Cornelius F.; Wall, Nathalie A.; Clark, Sue B.; Beyenal, Haluk
Abstract : The goals of this work were 1) to demonstrate lanthanum preconcentration/deposition on electrodes, 2) to elucidate the mechanism of deposition, and 3) to use electrodeposition to detect lanthanum on carbon fiber microelectrodes. Lanthanum was preconcentrated via electroprecipitation on carbon electrodes using unbuffered electrolyte. To measure the amount of La deposited on the surface, we used eQCM to observe the mass change (quantified as frequency change) while La precipitated on the surface of the electrode. The chemical state of the deposited film was determined using X-ray photoelectron spectrometry and Auger electron spectrometry. We used a pH microelectrode with a tip diameter of less than 20 μm near the electrode surface to determine surface pH changes. We found that lanthanum preconcentration on electrodes is a result of pH changes at the electrode surface due to water electrolysis. La(OH)3 was determined to be the predominant state of the film, with La and O atoms colocalized in the precipitates. Based on this discovery, the current responses to lanthanum electroprecipitation on carbon fiber microelectrodes and a mercury-filmed carbon fiber microelectrode were compared. We found that both microelectrode responses were concentration-dependent.